Authentic leadership: a paradigm for advancing ethical practices in teacher education - Edward Ojuok Okanda (Universitas PGRI Madiun, 2023)
The subject of authentic leadership continues to be largely unexplored, especially in the teacher education institutions, despite the reports of entrenched corruption, wastage of resources by leaders, and negative subordinate behaviours. This study aims to analyse how authentic leadership can promote ethical practices in primary teacher education in Kenya. Within the realm of phenomenological research design, semi-structured interviews were utilized as the data collection instrument. The respondents were 35 leaders from public primary teacher training colleges (TTCs) and regional education officers. The qualitative data of the interviews was analysed using thematic analysis. The findings indicated that authentic leadership generates trusted role models who have the capacity to promote ethical practices within primary TTCs. Finally, the study proposed a philosophical paradigm of authentic leadership based on moral rightness and moral goodness to influence the mind-set of individuals within TTCs to internalize ethical practices as a routine lifestyle